Monitor, Analyse and Consume Distributed Enterprise Machine Data using Splunk to Enhance Operation Intelligence - Rajesh Kumar Maurya, Kalpana Dwivedi,Bipin Tiwari, Devendra Kumar (International Journal of Advanced Science and Technology, 2020)
From the websites, applications, sensors, devices etc. the machine generated gathered data which makes up the IT infrastructure and business with the help of splunk is able to analyse, visualise and search the data. This paper is intended to explore and present the search, analytical, indexing and monitoring capability of Splunk. Splunk is a modern, efficient and scalable product which is used by many big enterprises to monitor and analyse their data generated across distributed machines. These data could include transactional, system generated, website access, application data, trouble shooting data, DB transaction logs and much more. It also covers the working architecture of Splunk and explain how Splunk server and client work in close collaboration to pull the machine data and index it into Splunk repository. Paper further covers about set of APIs available in Splunk that can be used by an external application to consume indexed data and also touches upon various data sources that Out of box Splunk support by providing pluggable and easily configurable applications.